BENEFICIATION STUDY OF RARE EARTH ORE USING FLOTATION, GRAVITY CONCENTRATION, AND MAGNETIC SEPARATION METHODS : A REVIEW - Muhammad Aulia, Fadly
Rare earth element (REE) is kind of metal that is widely used in industry such as electronics, energy, catalyst technology, and as alloying material for advance material in many others industries. The demand for rare earth is predicted to increase for every year. The presence of REE is associated with the other elements in rare earth minerals (REM) that deposited in rare earth ores. The beneficiation of rare earth ore is applied to increase recovery and grade of REM before extraction process. It purpose to reduce gangue minerals presence so the extraction process will be more effective and efficient. This literature study aims to review about rare earth ore and its beneficiation using flotation, gravity concentration, and magnetic separation method. This research begin with searching for literature on various sources such as internet sites, paper, articles, journals, and books. The literatur source that searched was about rare earth ore and its beneficiation methods. From the literatur that has been collected, analysis was carried out to eliminate the non relevant sources, so the literature that is appropriate to research topic was obtained. The rare earth ore beneficiation method that discussed in this research was flotation, gravity concentration, and magnetic separation. The data obtained from the literature was analyzed, discussed, and compared with the theory from literature to obtain the conclusion of this research objectives. Based on results of the review, it was found that between rare earth ore deposits have different mineralogy. It caused by difference in the deposit formation mechanism and the deposit source rock. In beneficiation of rare earth ore by flotation method, it was found that increasing collector concentration will increase REM recovery. At same concentration, sodium oleate was able to produce the highest recovery, while hydroxamate was the most selective collector on REM. With increasing depressant dose, recovery of REM rawill decreased. Sodium silicate depressant produce a higher REM recovery than starch, but with starch the enrichment ratio was higher than using the other depressant. Therefore, optimum pH for monazite and xenotime flotation was 7-9, while for baesnasite it was 8.5-10. On the effect of increasing the temperature during the flotation conditioning process, it was found that there was an increase in recovery and grade. For beneficiation process using a shaking table, highest recovery was obtained in medium size fraction (-75+38 ?m) and highest grade in coarse size fraction (-150 +75 ?m). Beside that, with ANOVA analysis it was found that table tilt angle has a significant effect on REM recovery and grade which vibration frequency was not significant. In beneficiation using multi-gravity concentrator, with Yates method and ANOVA analysis it was obtained that vibration frequency, vibration amplitude, and wash water flow were not have a significant effect on rare earth recovery and grade. For rare earth ore magnetic separation it was found that lower magnetic field intensity (0.4T) was optimal for separating ferromagnetic mineral from REM and higher magnetic field intensity (1.81T) was optimal for separating REM from diamagnetic and the other paramagnetic mineral.